Laminate for transferring circularly polarizing element and method for producing optical article using same

JP7652069B2Active Publication Date: 2025-03-27TOYOBO CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021522826
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-28
Filing Date
2020-05-27
Publication Date
2025-03-27
Estimated Expiration
2040-05-27

AI Technical Summary

Benefits of technology

【0009】 本発明により、画像表示装置のさらなる薄型化を可能にする。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007652069000001
    Figure 0007652069000001
  • Figure 0007652069000002
    Figure 0007652069000002
  • Figure 0007652069000003
    Figure 0007652069000003
Patent Text Reader

Abstract

Provided is a means for dealing with further thinned image processing devices. In this laminate for circular polarization element transfer, a polarizer and a λ / 4 retardation layer are laminated in this order on a releasable film, or a λ / 4 retardation layer and a polarizer are laminated in this order on the releasable film. It is possible to manufacture an image display device having a circular polarization element by transferring the laminate to a constituent member of the image display device.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate for transferring a circular polarization element, and a method for producing an optical article using the laminate (for example, a transparent conductive substrate having a circular polarization element, a touch panel having a circular polarization element, a transparent substrate for a surface cover having a circular polarization element, and an image display device having a circular polarization element). [Background technology]

[0002] In recent years, organic EL display devices have been attracting attention as image display devices in various fields. In particular, due to their thinness, organic EL display devices are expected not only to be used as a means for reducing the thickness and weight of large image display devices such as televisions, but also as curved image display devices and flexible image display devices.

[0003] In an organic EL display device, a circular polarizing plate is attached to the viewing side of an organic EL cell to prevent reflection from wiring, cells, etc. Conventionally, a circular polarizing plate has a structure in which a λ / 4 retardation film is attached to the organic EL cell side of the polarizing plate. A polarizing plate is a polarizer with a polarizer protective film attached to it. As the polarizer protective film, a rigid film of 40 to 100 μm such as triacetyl cellulose (TAC), acrylic resin, cyclic polyolefin (COP), polyethylene terephthalate (PET), etc. is used. In addition, as the λ / 4 retardation film, a film in which a resin having birefringence such as cyclic polyolefin or polycarbonate is stretched, or a film in which a liquid crystal compound layer is provided by coating on TAC is used.

[0004] A circular polarizing plate can also be made thinner by omitting the polarizer protective film on the λ / 4 retardation film side of the polarizing plate and directly laminating a λ / 4 retardation film on one side of the polarizer, but there is a limit to how thin the plate can be made using this method.

[0005] Organic EL display devices are often combined with touch panels (for example, Patent Documents 1 and 2), and in-vehicle or outdoor organic EL display devices (for example, car navigation systems, rear monitors, side monitors, instrument panels, etc.) are often provided with a transparent substrate for a surface cover, and therefore many components are provided, so there is a limit to how thin the organic EL display device can be made even if the organic EL display cell is made thin. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2017-84153 A [Patent Document 2] JP 2017-128004 A Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made in light of the problems with the conventional technology. That is, an object of the present invention is to provide a means for dealing with thinner image display devices. [Means for solving the problem]

[0008] The present inventors have conducted extensive research to achieve the above object, and as a result have completed the present invention. That is, the present invention includes the following aspects. Section 1. A laminate for transferring a circularly polarizing element, comprising a polarizer and a λ / 4 retardation layer laminated in this order on a release film, or a λ / 4 retardation layer and a polarizer laminated in this order on a release film. Section 2. A method for producing a transparent conductive substrate having a circular polarization element, comprising the steps of: (A) a step of laminating a laminate for transferring a circular polarization element, in which a polarizer and a λ / 4 retardation layer are laminated in this order on a release film, on a transparent conductive substrate so that the λ / 4 retardation layer of the laminate for transferring a circular polarization element is disposed on the transparent conductive substrate side; or (B) A step of laminating a laminate for transferring a circular polarization element, in which a λ / 4 retardation layer and a polarizer are laminated in this order on a release film, on a transparent conductive substrate so that the polarizer of the laminate for transferring a circular polarization element is disposed on the transparent conductive substrate side. A method comprising: Section 3. A method for manufacturing a touch panel having a circular polarization element, comprising the steps of: (C) laminating the laminate for transferring a circular polarization element, in which a polarizer and a λ / 4 retardation layer are laminated in this order on a release film, on a transparent conductive substrate of a touch panel such that the λ / 4 retardation layer of the laminate for transferring a circular polarization element is disposed on the transparent conductive substrate side; or (D) A step of laminating the laminate for transferring a circular polarization element, in which a λ / 4 retardation layer and a polarizer are laminated in this order on a release film, on a transparent conductive substrate of a touch panel, so that the polarizer of the laminate for transferring a circular polarization element is disposed on the transparent conductive substrate side. A method comprising: Section 4. A method for manufacturing an image display device having a circular polarization element, comprising the steps of: Item 4. A method comprising the step of providing a touch panel having a circular polarization element manufactured by the method of item 3 on an image display device so that the touch panel or the circular polarization element of the touch panel is disposed on the viewing side. Section 5. A method for producing a transparent substrate for a surface cover having a circular polarizing element, comprising the steps of: (E) A step of laminating the laminate for transferring a circularly polarizing element on a transparent substrate for a surface cover such that the λ / 4 retardation layer of the laminate for transferring a circularly polarizing element, which is formed by laminating a polarizer and a λ / 4 retardation layer in this order on a release film, is disposed on the transparent substrate side; or (F) A step of laminating the laminate for transferring a circular polarization element, in which a λ / 4 retardation layer and a polarizer are laminated in this order on a release film, on a transparent substrate for a surface cover, so that the polarizer of the laminate for transferring a circular polarization element is disposed on the transparent substrate side. A method comprising: Section 6. A method for manufacturing an image display device having a circular polarization element, comprising the steps of: Item 6. A method comprising the step of providing an image display device with a transparent substrate for a surface cover having a circular polarizing element, the transparent substrate being manufactured by the method according to item 5, such that the transparent substrate for a surface cover is disposed on the viewing side. Effect of the Invention

[0009] The present invention enables image display devices to be made even thinner. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] It is preferable that the laminate for transferring a circular polarization element of the present invention has a polarizer and a λ / 4 retardation layer laminated in this order on a release film, or a λ / 4 retardation layer and a polarizer laminated in this order on a release film.

[0011] The lamination order of the polarizer and the λ / 4 retardation layer can be selected depending on, for example, the position of the transfer target incorporated in the image display device. For example, if the order is image display cell-λ / 4 retardation layer-polarizer-transfer target, the lamination order is preferably release film-λ / 4 retardation layer-polarizer, and if the order is image display cell-transfer target-λ / 4 retardation layer-polarizer, the lamination order is preferably release film-polarizer-λ / 4 retardation layer.

[0012] (Release film) As the release film of the laminate for transferring a circularly polarizing element, a film widely used as a release film can be appropriately used. The release film is composed of a single layer or multiple layers, and includes at least a substrate film. The substrate film is preferably a resin film. The resin of the resin film is not particularly limited, and any resin film can be used without limitation, such as polyester, polycarbonate, polyamide, polyimide, polyamideimide, polystyrene, triacetyl cellulose, polypropylene, and cyclic polyolefin. Among these, polyester is preferable from the viewpoint of mechanical strength, heat resistance, supply stability, and the like, and polyethylene terephthalate is more preferable. In addition, the substrate film may be an unstretched film or a stretched film. When it is a stretched film, it may be a uniaxially stretched film or a biaxially stretched film. Among them, a biaxially stretched polyethylene terephthalate film is preferable.

[0013] When the substrate film itself has releasability, the substrate film can be used as it is as a releasable film. In order to adjust the releasability of the substrate film, the substrate film may be subjected to a surface treatment such as a corona treatment, a plasma treatment, or a flame treatment.

[0014] The release film may have a release layer on the base film. Examples of the release layer include silicone-based, amino resin-based, alkyd resin-based, long-chain acrylic resin-based, etc., and the composition and type can be appropriately selected according to the required release force.

[0015] The release film may have an easy-adhesion layer between the base film and the release layer. As the easy-adhesion layer, those conventionally used in each base film such as polyester-based, acrylic-based, and polyurethane-based can be used, and can be selected according to the base film and / or release layer to be used.

[0016] (Antistatic layer) The laminate for transferring a circularly polarizing element may have an antistatic layer on the release film. The antistatic layer is preferably provided between the substrate film and the release layer, or on the back surface (opposite side to the release surface) of the substrate film. It is also preferable that an antistatic agent is added to the release layer so that the release layer has antistatic properties.

[0017] The antistatic layer is not particularly limited as long as it is a layer containing an antistatic agent. Examples of the antistatic agent include cationic antistatic agents such as quaternary ammonium salts; conductive polymers such as polyaniline and polythiophene; needle-shaped metal fillers; and conductive high refractive index fine particles such as tin-doped indium oxide fine particles and antimony-doped tin oxide fine particles. The antistatic agent may be used alone or in combination of two or more.

[0018] The antistatic layer preferably contains a binder resin in addition to the antistatic agent. Examples of the binder resin include polyester, polyurethane, polyamide, and acrylic. Only one type of binder resin may be used, or two or more types may be used in combination.

[0019] (Polarizer) Examples of polarizers (also called polarizing plates, polarizing films, polarizing layers, etc.) that can be used include those in which iodine or an organic dichroic dye is adsorbed onto uniaxially stretched polyvinyl alcohol (PVA) (PVA polarizers), those in which a composition consisting of a liquid crystal compound and a dichroic dye is coated (or spread) and oriented (liquid crystal polarizers), and wire grid polarizers. In this specification, coating includes not only a wet process in which a liquid is coated and solidified, but also dry processes such as deposition, sputtering, and CVD.

[0020] As examples of a method for providing a polarizer on a λ / 4 retardation layer or a release film, in the case of a PVA polarizer, methods (a) and (b) can be mentioned. (a) A method of bonding individual PVA polarizers. (b) A method for transferring a PVA polarizer onto a releasable substrate.

[0021] The method (a) includes a method of laminating a PVA polarizer alone using an adhesive or pressure-sensitive adhesive, and a method of laminating a PVA polarizer to the release surface of a release film or the λ / 4 retardation layer on a release film using an adhesive or pressure-sensitive adhesive is preferred. The thickness of this type of polarizer is preferably 5 to 50 μm, more preferably 10 to 30 μm, and particularly preferably 12 to 25 μm. The thickness of the adhesive or pressure-sensitive adhesive is preferably 1 to 10 μm, and more preferably 2 to 5 μm.

[0022] In the method (b), the releasable substrate may be any of those listed as the releasable film, and preferably is an unstretched or uniaxially stretched film such as PET or polypropylene. A method for laminating a PVA polarizer on a releasable substrate may include a method in which PVA is coated on the releasable substrate, and the substrate is stretched together with the releasable substrate to allow iodine or an organic dichroic dye to be adsorbed on the PVA, and then the orientation is fixed with a boron compound. In this specification, a laminate of a releasable substrate and a PVA polarizer may be referred to as a "PVA polarizer transfer laminate".

[0023] If the circularly polarizing element transfer laminate is one in which the release film-polarizer-λ / 4 retardation layer are laminated in this order, the polarizer of the PVA polarizer transfer laminate may be transferred to the release surface of the release film to form a "release film-polarizer", but it is preferable to use the PVA polarizer transfer laminate as it is as a "release film-polarizer". Also, if the circularly polarizing element transfer laminate is one in which the release film-λ / 4 retardation layer-polarizer are laminated in this order, it is preferable to transfer the polarizer of the PVA polarizer transfer laminate to the λ / 4 retardation layer on the release film. As a transfer method, a method in which the λ / 4 retardation layer on the release film is attached to the polarizer surface (surface on which the release substrate is not laminated) of the PVA polarizer transfer laminate with an adhesive or pressure-sensitive adhesive, and the release substrate is peeled off as necessary, can be mentioned. The thickness of this type of polarizer is preferably 1 to 10 μm, more preferably 2 to 8 μm, and particularly preferably 3 to 6 μm. The thickness of the adhesive or pressure sensitive adhesive is preferably 1 to 10 μm, and more preferably 2 to 5 μm.

[0024] The adhesive used for lamination is preferably a polyvinyl alcohol adhesive, an ultraviolet-curing adhesive such as acrylic or epoxy, or a heat-curing adhesive such as epoxy or isocyanate (urethane). The adhesive may also be a hot melt adhesive. Examples of the pressure-sensitive adhesive include acrylic, urethane, and rubber-based adhesives. It is also preferable to use an acrylic-based, substrate-less optical transparent pressure-sensitive adhesive sheet as the pressure-sensitive adhesive.

[0025] As examples of the method for providing a polarizer on the λ / 4 retardation layer or the release film, in the case of a liquid crystal polarizer, methods (c) and (d) can be mentioned. (c) A method for applying paint for liquid crystal polarizers. (d) A method of transferring a liquid crystal polarizer on a releasable substrate.

[0026] As the method (c), a liquid crystal polarizer coating material containing a liquid crystal compound is applied to the release surface of a release film or the λ / 4 retardation layer on the release film, and the liquid crystal compound is aligned and fixed. As a method for aligning and fixing a liquid crystal compound, a method for applying a liquid crystal polarizer coating material to a surface that has been subjected to a rubbing treatment, heating to align the coating material, and then curing and fixing the coating material with ultraviolet light; a method for irradiating the coating material with polarized ultraviolet light after applying the coating material for a liquid crystal polarizer, and then aligning and fixing the liquid crystal compound, and the like, are included. In addition, it is also a preferred method to provide an orientation control layer on the release surface of a release film or the λ / 4 retardation layer on the release film before applying the coating material for a liquid crystal polarizer, that is, to laminate a liquid crystal polarizer on the release surface of a release film or the λ / 4 retardation layer on the release film via an orientation control layer.

[0027] The method (d) includes a method of laminating a liquid crystal polarizer on a releasable substrate in accordance with the above method (c), laminating the release surface of a release film or the λ / 4 retardation layer on the release film using an adhesive or pressure-sensitive adhesive, and peeling off the release substrate as necessary. The adhesive and pressure-sensitive adhesive used in lamination include those mentioned above. The release substrate may be one of those listed as the release substrate for the PVA polarizer transfer laminate, a metal belt, or the like. In this specification, a laminate of a release substrate and a liquid crystal polarizer may be referred to as a "liquid crystal polarizer transfer laminate".

[0028] The thickness of the liquid crystal polarizer is preferably from 0.1 to 7 μm, more preferably from 0.3 to 5 μm, and particularly preferably from 0.5 to 3 μm. The thickness of the adhesive or pressure-sensitive adhesive is preferably from 1 to 10 μm, and more preferably from 2 to 5 μm.

[0029] Furthermore, the alignment control layer and the liquid crystal polarizer will be described in detail. (Orientation control layer) The liquid crystal polarizer coating material may be directly applied to a release film or a λ / 4 retardation layer, but it is also preferable to provide an orientation control layer in advance and then apply the coating material onto the orientation control layer. In this specification, the orientation control layer and the liquid crystal polarizer are regarded as a single member, and the member may be called a liquid crystal polarizer. The liquid crystal polarizer combined with the orientation control layer may be called a liquid crystal polarizing layer in order to clearly distinguish it from the general term liquid crystal polarizer.

[0030] The alignment control layer may be any layer that can cause the liquid crystal compound to be aligned in a desired state. Suitable examples of the alignment control layer include a rubbed alignment control layer having a rubbing treatment on the surface and a photoalignment control layer that aligns the molecules by irradiating them with polarized light to produce an alignment function.

[0031] (Rubbing treatment alignment control layer) The material of the rubbing treatment alignment control layer is usually a polymer. As the polymer, polyvinyl alcohol and its derivatives, polyimide and its derivatives, acrylic resin, polysiloxane derivatives, etc. are preferably used. Only one type of polymer may be used, or two or more types may be used in combination.

[0032] The method for forming the rubbing treatment alignment control layer is preferably a method including a step of applying a coating material for the rubbing treatment alignment control layer containing the above-mentioned polymer and solvent to a release film or a λ / 4 retardation layer, and subjecting the surface of the coating film to a rubbing treatment. The coating material for the rubbing treatment alignment control layer may contain a crosslinking agent.

[0033] The solvent for the coating material for the rubbing treatment alignment control layer can be used without any restrictions as long as it dissolves the polymer material. Specific examples include alcohols such as water, methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, and cellosolve; ester-based solvents such as ethyl acetate, butyl acetate, and gamma-butyrolactone; ketone-based solvents such as acetone, methyl ethyl ketone, cyclopentanone, and cyclohexanone; aromatic hydrocarbon solvents such as toluene and xylene; and ether-based solvents such as tetrahydrofuran and dimethoxyethane. Only one type of solvent may be used, or two or more types may be used in combination.

[0034] The concentration of the polymer in the coating material for the rubbing treatment alignment control layer can be adjusted appropriately depending on the type of polymer and the thickness of the alignment control layer to be produced, but it is preferable that the solid content concentration be 0.2 to 20 mass %, and a range of 0.3 to 10 mass % is particularly preferable.

[0035] As the application method, a known method can be used, such as application methods including gravure coating, die coating, bar coating, and applicator methods, and printing methods including flexography.

[0036] After application, it is preferable to dry (for example, heat drying). The drying temperature depends on the material of the release film, but in the case of PET, it is preferably 30°C to 170°C, more preferably 50°C to 150°C, and even more preferably 70°C to 130°C. If the drying temperature is in this range, there is no need to take a long drying time, and productivity is excellent, there is no thermal elongation or thermal shrinkage of the transfer orientation film, the optical function as designed can be achieved, and the flatness is also excellent. The drying time is, for example, 0.5 to 30 minutes, more preferably 1 to 20 minutes, and even more preferably 2 to 10 minutes.

[0037] The thickness of the rubbing treatment alignment control layer is preferably 0.01 to 10 μm, more preferably 0.05 to 5 μm, and particularly preferably 0.1 to 1 μm.

[0038] The rubbing treatment can generally be carried out by rubbing the surface with paper or cloth in a certain direction. The rubbing treatment is preferably carried out using a rubbing roller made of raised cloth made of fibers such as nylon, polyester, and acrylic. When an orientation control layer is provided that is oriented in a specific direction oblique to the longitudinal direction of a long film, the rubbing direction is preferably set at an angle that matches the direction. The angle can be adjusted by adjusting the angle between the rubbing roller and the film, the film transport speed, and the number of rotations of the roller, etc.

[0039] (Photo alignment control layer) The photo-alignment control layer is preferably an alignment film in which a coating material (a coating material for photo-alignment control layer) containing a polymer and / or monomer having a photoreactive group and a solvent is applied to a release film or a λ / 4 retardation layer, and then polarized light, preferably polarized ultraviolet light, is applied to the layer to impart an alignment control force. The photoreactive group is preferably a group that generates a liquid crystal alignment ability by irradiation with light, and specifically, is preferably a group that generates a photoreaction that is the origin of the liquid crystal alignment ability, such as molecular orientation induction or isomerization reaction, dimerization reaction, photocrosslinking reaction, or photodecomposition reaction, which occurs by irradiation with light. Among the photoreactive groups, those that cause a dimerization reaction or a photocrosslinking reaction are preferred in terms of excellent alignment and maintaining the smectic liquid crystal state. The photoreactive group that can cause the above-mentioned reaction is preferably an unsaturated bond, particularly a double bond, and is particularly preferably a group having at least one selected from the group consisting of a C=C bond, a C=N bond, an N=N bond, and a C=O bond.

[0040] Examples of photoreactive groups having a C=C bond include vinyl groups, polyene groups, stilbene groups, stilbazolyl groups, stilbazolium groups, chalcone groups, and cinnamoyl groups. Examples of photoreactive groups having a C=N bond include groups having structures such as aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups having an N=N bond include azobenzene groups, azonaphthalene groups, aromatic heterocyclic azo groups, bisazo groups, formazan groups, and groups having azoxybenzene as a basic structure. Examples of photoreactive groups having a C=O bond include benzophenone groups, coumarin groups, anthraquinone groups, and maleimide groups. These groups may have substituents such as alkyl groups, alkoxy groups, aryl groups, allyloxy groups, cyano groups, alkoxycarbonyl groups, hydroxyl groups, sulfonic acid groups, and halogenated alkyl groups. The number of substituents is not particularly limited, and may be, for example, 1, 2, 3, or 4.

[0041] Among them, photoreactive groups capable of photodimerization are preferred, and cinnamoyl and chalcone groups are preferred because the amount of polarized light irradiation required for photoalignment is relatively small, and a photoalignment control layer having excellent thermal stability and stability over time is easily obtained. Furthermore, as the polymer having a photoreactive group, one having a cinnamoyl group such that the terminal of the polymer side chain has a cinnamic acid structure is particularly preferred. Examples of the main chain structure include polyimide, polyamide, (meth)acrylic, and polyester.

[0042] Specific examples of the orientation control layer include those described in JP-A-2006-285197, JP-A-2007-76839, JP-A-2007-138138, JP-A-2007-94071, JP-A-2007-121721, JP-A-2007-140465, JP-A-2007-156439, JP-A-2007-133184, and JP-A-2009 Examples of the orientation control layers include those described in JP-A-109831, JP-A-2002-229039, JP-A-2002-265541, JP-A-2002-317013, JP-T-2003-520878, JP-T-2004-529220, JP-A-2013-33248, JP-A-2015-7702, and JP-A-2015-129210.

[0043] The solvent for the coating material for the photo-alignment control layer can be any solvent that dissolves the polymer and monomer having a photoreactive group. Specific examples include those mentioned in the method for forming the alignment control layer by rubbing treatment. It is also preferable to add a photopolymerization initiator, a polymerization inhibitor, and various stabilizers to the coating material for the photo-alignment control layer. In addition, the coating material for the photo-alignment control layer may contain polymers other than the polymer and monomer having a photoreactive group, and monomers that do not have a photoreactive group and are copolymerizable with the monomer having a photoreactive group.

[0044] The concentration of the polymer or monomer of the coating material for the photo-alignment control layer, the coating method, and the drying conditions can be the same as those mentioned in the formation method of the rubbing treatment alignment control layer. The preferred thickness is also the same as that of the rubbing treatment alignment control layer.

[0045] It is preferable that the polarized light is irradiated from the direction of the surface of the photo-alignment control layer before alignment.

[0046] The wavelength of the polarized light is preferably in a wavelength range where the photoreactive group of the polymer or monomer having the photoreactive group can absorb light energy. Specifically, ultraviolet light having a wavelength of 250 to 400 nm is preferable. Examples of the light source of the polarized light include a xenon lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a metal halide lamp, and an ultraviolet laser such as KrF or ArF, and the high-pressure mercury lamp, the ultra-high-pressure mercury lamp, and the metal halide lamp are preferable.

[0047] Polarized light can be obtained, for example, by passing the light from the light source through a polarizer. The direction of polarization can be adjusted by adjusting the polarization angle of the polarizer. Examples of polarizers include polarizing filters, polarizing prisms such as Glan-Thompson and Glan-Taylor, and wire grid type polarizers. It is preferable that the polarized light is substantially parallel light.

[0048] By adjusting the angle of the irradiated polarized light, the direction of the alignment regulating force of the photoalignment layer can be adjusted as desired.

[0049] The irradiation intensity varies depending on the type and amount of polymerization initiator and resin (monomer), but for example, it is 10 to 10,000 mJ / cm at 365 nm. 2 is preferable, and more preferably 20 to 5000 mJ / cm 2 is preferred.

[0050] (Liquid crystal polarizer) The liquid crystal polarizer functions as a polarizer that transmits light in only one direction, and preferably contains a dichroic dye.

[0051] <Dichroic dye> The dichroic dye is preferably an organic dye having different absorbance in the long axis direction and in the short axis direction of the molecule.

[0052] The dichroic dye preferably has a maximum absorption wavelength (λMAX) in the range of 300 to 700 nm. Examples of such dichroic dyes include acridine dyes, oxazine dyes, cyanine dyes, naphthalene dyes, azo dyes, and anthraquinone dyes, and among these, azo dyes are preferred. Examples of azo dyes include monoazo dyes, bisazo dyes, trisazo dyes, tetrakisazo dyes, and stilbene azo dyes, and are preferably bisazo dyes and / or trisazo dyes. The dichroic dyes may be used alone or in combination of two or more kinds, but in order to adjust the color tone (achromatic color), it is preferable to combine two or more kinds. In particular, it is preferable to combine three or more kinds. In particular, it is preferable to combine three or more kinds of azo compounds.

[0053] Preferred azo compounds include dyes described in JP-A-2007-126628, JP-A-2010-168570, JP-A-2013-101328, and JP-A-2013-210624.

[0054] The dichroic dye is preferably a dichroic dye polymer introduced into the side chain of a polymer such as an acrylic polymer. Examples of the dichroic dye polymer include the polymers described in JP-A-2016-4055 and the polymers obtained by polymerizing the compounds of [Chemical formula 6] to [Chemical formula 12] in JP-A-2014-206682.

[0055] From the viewpoint of obtaining good alignment of the dichroic dye, the content of the dichroic dye in the liquid crystal polarizer is preferably from 0.1 to 30 mass %, more preferably from 0.5 to 20 mass %, further preferably from 1.0 to 15 mass %, and particularly preferably from 2.0 to 10 mass %.

[0056] The liquid crystal polarizer preferably further contains a polymerizable liquid crystal compound in order to improve the film strength, polarization degree, and film uniformity. The polymerizable liquid crystal compound also includes a polymerized film.

[0057] <Polymerizable liquid crystal compound> The polymerizable liquid crystal compound is preferably a compound that has a polymerizable group and exhibits liquid crystallinity. The polymerizable group means a group involved in a polymerization reaction, and is preferably a photopolymerizable group. Here, the photopolymerizable group means a group that can undergo a polymerization reaction by an active radical, an acid, or the like generated from a photopolymerization initiator described later. Examples of the polymerizable group include a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, and an oxetanyl group. Among them, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferred, and an acryloyloxy group is more preferred. The compound exhibiting liquid crystallinity may be a thermotropic liquid crystal or a lyotropic liquid crystal. The thermotropic liquid crystal may be a nematic liquid crystal or a smectic liquid crystal.

[0058] The polymerizable liquid crystal compound is preferably a smectic liquid crystal compound, and more preferably a high-order smectic liquid crystal compound, in that higher polarization properties can be obtained. When the liquid crystal phase formed by the polymerizable liquid crystal compound is a high-order smectic phase, a liquid crystal polarizer with a higher degree of orientation order can be produced.

[0059] Specific preferred polymerizable liquid crystal compounds include those described in, for example, JP2002-308832A, JP2007-16207A, JP2015-163596A, JP2007-510946A, JP2013-114131A, WO2005 / 045485A, Lub et al. Recl. Trav. Chim. Pays-Bas, 115, 321-328(1996), and the like.

[0060] From the viewpoint of increasing the alignment property of the polymerizable liquid crystal compound, the content of the polymerizable liquid crystal compound in the liquid crystal polarizer is preferably 70 to 99.5 mass %, more preferably 75 to 99 mass %, even more preferably 80 to 97 mass %, and particularly preferably 83 to 95 mass %.

[0061] The liquid crystal polarizer can be provided by applying a coating material for liquid crystal polarizers. The coating material for liquid crystal polarizers may contain additives such as a solvent, a polymerization initiator, a sensitizer, a polymerization inhibitor, a leveling agent, a polymerizable non-liquid crystal compound, a crosslinking agent, etc. The additives may be used alone or in combination of two or more kinds.

[0062] As the solvent, those exemplified as the solvent for the coating material for the alignment control layer are preferably used.

[0063] The polymerization initiator is not limited as long as it polymerizes the polymerizable liquid crystal compound, but a photopolymerization initiator that generates active radicals by light is preferable. Examples of the polymerization initiator include benzoin compounds, benzophenone compounds, alkylphenone compounds, acylphosphine oxide compounds, triazine compounds, iodonium salts, and sulfonium salts.

[0064] The sensitizer is preferably a photosensitizer, and examples thereof include a xanthone compound, an anthracene compound, phenothiazine, and rubrene.

[0065] Examples of the polymerization inhibitor include hydroquinones, catechols, and thiophenols.

[0066] The polymerizable non-liquid crystal compound is preferably one that copolymerizes with the polymerizable liquid crystal compound, and for example, when the polymerizable liquid crystal compound has a (meth)acryloyloxy group, (meth)acrylates can be mentioned. The (meth)acrylates may be monofunctional or polyfunctional. By using polyfunctional (meth)acrylates, the strength of the polarizer can be improved. When a polymerizable non-liquid crystal compound is used, the content thereof in the liquid crystal polarizer is preferably 1 to 15% by mass, more preferably 2 to 10% by mass, and particularly preferably 3 to 7% by mass, in order to suppress a decrease in the degree of polarization.

[0067] Examples of the crosslinking agent include compounds capable of reacting with functional groups of the polymerizable liquid crystal compound and the polymerizable non-liquid crystal compound, such as isocyanate compounds, melamine, epoxy resins, and oxazoline compounds.

[0068] The liquid crystal polarizer coating material can be applied onto a release film, a λ / 4 retardation layer, or an alignment control layer, and then dried, heated, and cured as necessary to produce a liquid crystal polarizer.

[0069] The coating method may be a known method such as a coating method such as a gravure coating method, a die coating method, a bar coating method or an applicator method, or a printing method such as a flexography method.

[0070] Drying is preferably carried out in a dryer (such as a hot air dryer or an infrared dryer) at a temperature of 30 to 170° C. The drying temperature is more preferably 50 to 150° C., and even more preferably 70 to 130° C., and the drying time is preferably 0.5 to 30 minutes, more preferably 1 to 20 minutes, and even more preferably 2 to 10 minutes.

[0071] In order to more firmly align the dichroic dye and the polymerizable liquid crystal compound in the liquid crystal polarizer, heating can be performed. The heating temperature is preferably set to a temperature range in which the polymerizable liquid crystal compound forms a liquid crystal phase.

[0072] When the liquid crystal polarizer coating material contains a polymerizable liquid crystal compound, it is preferable to cure it. Examples of the curing method include heating and light irradiation, and light irradiation is preferable. The dichroic dye can be fixed in an oriented state by curing. Curing is preferably performed in a state in which a liquid crystal phase is formed in the polymerizable liquid crystal compound, and may be cured by light irradiation at a temperature at which the liquid crystal phase is exhibited. Examples of light for light irradiation include visible light, ultraviolet light, and laser light. In terms of ease of handling, ultraviolet light is preferable.

[0073] The irradiation intensity varies depending on the type and amount of polymerization initiator and resin (monomer), but for example, it is 100 to 10,000 mJ / cm at 365 nm. 2 is preferable, and more preferably 200 to 5000 mJ / cm2 is preferred.

[0074] When a liquid crystal polarizer coating is applied onto an alignment control layer, the pigment is aligned along the alignment direction of the alignment layer, resulting in a liquid crystal polarizer having a polarization transmission axis in a predetermined direction. However, if an alignment control layer is not provided, the liquid crystal polarizer can also be aligned by irradiating polarized light to harden the liquid crystal compound-containing composition.

[0075] Any method may be used for providing the polarizer, but methods (b), (c) and (d) are particularly preferred.

[0076] (λ / 4 retardation layer) The λ / 4 retardation layer can convert the linearly polarized light by the polarizer into circularly polarized light. As the λ / 4 retardation layer, a coating layer coated with a coating material for the λ / 4 retardation layer is preferable, a coating layer coated with a coating material containing a liquid crystal compound or a polymer compound is more preferable, and a coating layer coated with a coating material containing a liquid crystal compound is particularly preferable.

[0077] Examples of polymer compounds used in the λ / 4 retardation layer include polymers having at least one aromatic ring in the repeating unit, such as polyimide, polyamideimide, polyester, polyetherketone, polyaryletherketone, and polyesterimide.

[0078] The liquid crystal compound used in the λ / 4 retardation layer is preferably a rod-like liquid crystal compound, and is preferably a polymerizable rod-like liquid crystal compound having a polymerizable group such as a double bond, in terms of being able to fix the alignment state.

[0079] Examples of the rod-shaped liquid crystal compound include rod-shaped liquid crystal compounds having a polymerizable group described in JP-A-2002-030042, JP-A-2004-204190, JP-A-2005-263789, JP-A-2007-119415, JP-A-2007-186430, and JP-A-11-513360.

[0080] Specific examples of rod-shaped liquid crystal compounds include: CH2=CHCOO-(CH2) m -O-Ph1-COO-Ph2-OCO-Ph1-O-(CH2) n -OCO-CH=CH2 CH2=CHCOO-(CH2) m -O-Ph1-COO-NPh-OCO-Ph1-O-(CH2) n -OCO-CH=CH2 CH2=CHCOO-(CH2) m -O-Ph1-COO-Ph2-OCH3 CH2=CHCOO-(CH2) m -O-Ph1-COO-Ph1-Ph1-CH2CH(CH3)C2H5 (In the formula, m and n are integers from 2 to 6; Ph1 and Ph2 are 1,4-phenylene groups (Ph2 may be substituted with a methyl group at the 2-position), NPh is the 2,6-naphthylene group. Examples include:

[0081] These rod-shaped liquid crystal compounds are commercially available as LC242 manufactured by BASF, and these compounds can be used.

[0082] These rod-shaped liquid crystal compounds may be used in combination of two or more kinds in any ratio.

[0083] The method for forming the λ / 4 retardation layer may be a method of applying a coating material for the λ / 4 retardation layer to the release surface of a release film or a polarizer on a release film, or a method of transferring the λ / 4 retardation layer on a release substrate to a polarizer. The laminate of the release substrate and the λ / 4 retardation layer may be called a "laminate for transferring retardation layer". The release substrate for the laminate for transferring retardation layer may be one listed as the release substrate for the laminate for PVA polarizer.

[0084] The coating material for the λ / 4 retardation layer may contain a solvent, a polymerization initiator, a sensitizer, a polymerization inhibitor, a leveling agent, a polymerizable non-liquid crystal compound, a crosslinking agent, etc. These can be those described in the alignment control layer or the liquid crystal polarizer.

[0085] The method of orienting the liquid crystal compound used in the λ / 4 retardation layer can be the same as the method of orienting the liquid crystal polarizer described above. That is, the method of directly applying the coating material for the λ / 4 retardation layer to a release film or a polarizer and irradiating it with polarized ultraviolet light, the method of rubbing the surface of the release film or the polarizer, the method of providing an orientation control layer between the polarizer and the λ / 4 retardation layer, etc. are included. Among these conditions, the conditions described for the orientation control layer or the liquid crystal polarizer are preferably used.

[0086] The λ / 4 retardation layer may be a single layer λ / 4 retardation layer, or a composite λ / 4 retardation layer of a λ / 4 retardation layer and a λ / 2 retardation layer. In this specification, the single layer λ / 4 retardation layer and the composite λ / 4 retardation layer may be collectively referred to as the λ / 4 retardation layer, and further, other retardation layers such as a C plate layer described later may also be collectively referred to as the λ / 4 retardation layer.

[0087] The in-plane retardation of the λ / 4 retardation layer is preferably 100 to 180 nm, more preferably 120 to 150 nm, and the in-plane retardation of the λ / 2 retardation layer is preferably 200 to 360 nm, more preferably 240 to 300 nm.

[0088] (angle of slow axis of λ / 4 retardation layer) In the case of a single λ / 4 retardation layer, the angle between the alignment axis (slow axis) of the λ / 4 retardation layer and the transmission axis of the polarizer is preferably 35 to 55 degrees, more preferably 40 to 50 degrees, and further preferably 42 to 48 degrees.

[0089] In the case of a composite λ / 4 retardation layer in which a λ / 4 retardation layer and a λ / 2 retardation layer are combined, it is preferable that the alignment axis (slow axis) of each retardation layer is arranged at an angle such that both layers have a retardation of λ / 4. Specifically, the angle (θ) between the alignment axis (slow axis) of the λ / 2 retardation layer and the transmission axis of the polarizer is preferably 5 to 20 degrees, more preferably 7 to 17 degrees. The angle between the alignment axis (slow axis) of the λ / 2 retardation layer and the alignment axis (slow axis) of the λ / 4 retardation layer is preferably in the range of 2θ+45 degrees±10 degrees, more preferably in the range of 2θ+45 degrees±5 degrees, and even more preferably in the range of 2θ+45 degrees±3 degrees.

[0090] Examples of the λ / 4 retardation layer can be found in JP2008-149577A, JP2002-303722A, WO2006 / 100830A, JP2015-64418A, JP2018-10086A, and the like.

[0091] Furthermore, in order to reduce the change in color when viewed from an oblique angle, it is also a preferred embodiment to provide a C plate layer on the λ / 4 retardation layer. As the C plate layer, a positive or negative C plate layer is selected according to the characteristics of the λ / 4 retardation layer and the λ / 2 retardation layer.

[0092] In the composite λ / 4 retardation layer, for example, a lamination method of a λ / 4 retardation layer and a λ / 2 retardation layer can be, for example, A method in which a λ / 2 retardation layer is formed on a polarizer by transfer, and then a λ / 4 retardation layer is formed on top of that by transfer. A method in which a λ / 2 retardation layer is formed on a polarizer by transfer, and then a λ / 4 retardation layer is formed on top of that by coating. A method in which a λ / 2 retardation layer is formed on a polarizer by coating, and a λ / 4 retardation layer is then formed on top of the layer by transfer. A method of providing a λ / 2 retardation layer and a λ / 4 retardation layer on a polarizer by coating A method in which a λ / 4 retardation layer and a λ / 2 retardation layer are provided in this order on a release substrate, and then these are transferred onto a polarizer. Examples include:

[0093] As a method for laminating a C plate on a λ / 4 retardation layer, various methods can be used, such as a method of providing a C plate layer on a λ / 4 retardation layer by transfer, a method of providing a C plate layer on a releasable substrate, and further providing a single λ / 4 retardation layer or a composite λ / 4 retardation layer thereon, and then transferring them to a polarizer.

[0094] (interlayer protective layer) The laminate for transferring a circularly polarizing element may have an interlayer protective layer between any two layers (for example, between a polarizer and a λ / 4 retardation layer, a surface of a λ / 4 retardation layer on which a polarizer is not laminated, between a plurality of retardation layers, between an adhesive or pressure-sensitive adhesive and a polarizer or a λ / 4 retardation layer). The interlayer protective layer can prevent a decrease in the degree of polarization or a change in retardation caused by the migration of components or solvents used in each layer to adjacent layers. The interlayer protective layer may be provided on a releasable substrate together with the λ / 4 retardation layer and / or the polarizer and transferred to a target.

[0095] Examples of the interlayer protective layer include a transparent resin layer. Examples of the transparent resin include, but are not limited to, polyvinyl alcohol, ethylene vinyl alcohol copolymer, polyester, polyurethane, polyamide, polystyrene, acrylic resin, and epoxy resin. The transparent resin may be crosslinked with a crosslinking agent to form a crosslinked structure. The transparent resin may also be a hard coat made by curing (for example, photocuring) a curable (for example, photocurable) composition such as acrylic. The interlayer protective layer may also serve as an orientation control layer.

[0096] The laminate for transferring a circularly polarizing element may have a masking film attached to the surface to be transferred (polarizer surface or λ / 4 retardation layer surface, etc.) to protect the surface. As the masking film, a film having an acrylic, rubber, polyolefin, or other adhesive layer provided on a substrate such as polyethylene, polypropylene, or polyester is preferably used. Instead of the masking film, a releasable substrate used when transferring the polarizer or λ / 4 retardation layer, etc. may remain.

[0097] The circular polarization element transfer laminate can be transferred to the surface of an object to provide a circular polarization element including a λ / 4 retardation layer and a polarizer on the surface of the object. When transferring to an object, the above-mentioned adhesive or pressure-sensitive adhesive can be used. The adhesive or pressure-sensitive adhesive for transferring to the object may be provided in advance on the circular polarization element transfer laminate. In this case, a separator may be further laminated on the adhesive layer or pressure-sensitive adhesive layer. The separator may be one of those listed in the releasable substrate of the PVA polarizer transfer laminate. It is preferable that the releasable substrate and the masking film are peeled off immediately before transferring to the object or immediately before providing the adhesive layer or pressure-sensitive adhesive layer.

[0098] It is preferable that the laminate for transferring a circularly polarizing element does not have a self-supporting film as a constituent layer other than the film for the manufacturing process. The self-supporting film is a film that is independently manufactured. Examples of the self-supporting film include a polarizer protective film. The film for the manufacturing process is a member that is used for the manufacture of the laminate for transferring a circularly polarizing element, but is ultimately removed in the image display device, and examples of the film include a release film, a release substrate, a masking film, and a separator. Each layer constituting the laminate for transferring a circularly polarizing element other than the film for the manufacturing process does not exist by itself, and is preferably provided by coating or transfer. This allows for further reduction in thickness and weight.

[0099] (Transcription subject) Examples of the object on which the circular polarizing element is provided using the laminate for transferring the circular polarizing element include, but are not limited to, the substance itself that causes reflection, and a transparent object that exists between the substance that causes reflection and the observer. Preferred objects include a transparent conductive substrate and a transparent substrate for a surface cover.

[0100] A circular polarization element can be provided on the surface of a target by laminating the circular polarization element transfer laminate on the surface of the target so that the λ / 4 retardation layer or polarizer of the circular polarization element transfer laminate is disposed on the surface of the target, and peeling off the release film. Note that the release film of the circular polarization element transfer laminate does not need to be peeled off immediately after lamination, and may be left unpeeled for surface protection until the final form is reached (or until use), and may be peeled off immediately before the final form is reached (or immediately before use).

[0101] (Transparent conductive substrate having a circular polarizing element) The transparent conductive substrate having a circular polarizing element is preferably one in which a laminate for transferring a circular polarizing element is laminated (transferred) onto a transparent conductive substrate. The transparent conductive substrate is preferably one in which a transparent conductive layer is provided on at least one side (preferably both sides) of the transparent substrate. Examples of the transparent substrate include glass, PET, TAC, COP, acrylic, polycarbonate, and other resin films. Examples of the transparent conductive layer include tin-doped indium oxide, metal mesh, conductive paste mesh, and resin coats in which needle-shaped metal fillers or CNTs are dispersed. By laminating a circular polarizing element onto a transparent conductive substrate using a laminate for transferring a circular polarizing element, the transparent conductive substrate can be provided with an anti-reflection function due to the circular polarizing element without substantially increasing the thickness.

[0102] In one embodiment, a method for producing a transparent conductive substrate having a circular polarizing element includes the steps of: (A) a step of laminating a laminate for transferring a circular polarization element, in which a polarizer and a λ / 4 retardation layer are laminated in this order on a release film, on a transparent conductive substrate so that the λ / 4 retardation layer of the laminate for transferring a circular polarization element is disposed on the transparent conductive substrate side; or (B) A step of laminating a laminate for transferring a circular polarization element, in which a λ / 4 retardation layer and a polarizer are laminated in this order on a release film, on a transparent conductive substrate so that the polarizer of the laminate for transferring a circular polarization element is disposed on the transparent conductive substrate side. It is preferred that the compound contains

[0103] (Touch panel with circular polarizing element) The touch panel having a circular polarizing element is preferably one in which a laminate for transferring a circular polarizing element is laminated (transferred) onto a transparent conductive substrate of the touch panel. The transparent conductive substrate may be the same as that described above. By laminating a circular polarizing element onto a transparent conductive substrate of a touch panel using the laminate for transferring a circular polarizing element, the touch panel can be provided with an anti-reflection function due to the circular polarizing element without substantially increasing the thickness.

[0104] The circular polarization element may be provided on either the transparent substrate side or the transparent conductive layer side of the transparent conductive substrate. In addition, when a coating layer or the like is present on the transparent conductive layer, the circular polarization element may be provided on the coating layer or the like.

[0105] A circular polarizing element may be provided on the transparent conductive substrate before processing into a touch panel, or may be provided at an intermediate stage of processing into a touch panel, or after processing. The circular polarizing element may be provided on the viewing side of the touch panel, or on the opposite side (the side facing the image display cell). In addition, in the case of a capacitive touch panel, the circular polarizing element may be present as a part of a dielectric layer between two transparent conductive substrates.

[0106] When an image display cell is laminated on a touch panel, the circular polarizing element may be present as an intermediate layer between the touch panel and the image display cell.When a surface cover is laminated on a touch panel, the circular polarizing element may be present as an intermediate layer between the touch panel and the surface cover.

[0107] In one embodiment, a method for producing a touch panel having a circular polarizing element includes the steps of: (C) laminating the laminate for transferring a circular polarization element, in which a polarizer and a λ / 4 retardation layer are laminated in this order on a release film, on a transparent conductive substrate of a touch panel such that the λ / 4 retardation layer of the laminate for transferring a circular polarization element is disposed on the transparent conductive substrate side; or (D) A step of laminating the laminate for transferring a circular polarization element, in which a λ / 4 retardation layer and a polarizer are laminated in this order on a release film, on a transparent conductive substrate of a touch panel, so that the polarizer of the laminate for transferring a circular polarization element is disposed on the transparent conductive substrate side. It is preferred that the compound contains

[0108] (Transparent substrate for surface cover) The transparent substrate for a surface cover having a circular polarizing element is preferably a substrate in which a laminate for transferring a circular polarizing element is laminated (transferred) onto the transparent substrate for a surface cover. Examples of the transparent substrate for a surface cover include a glass plate, a film or sheet of acrylic, polyester, polycarbonate, polystyrene, polypropylene, polymethylpentene, polyurethane, etc.

[0109] When an image display cell is laminated on the surface cover, the circular polarizing element may be present as an intermediate layer between the surface cover and the image display cell.

[0110] In one embodiment, a method for producing a transparent substrate for a surface cover having a circular polarizing element includes the steps of: (E) A step of laminating the laminate for transferring a circularly polarizing element on a transparent substrate for a surface cover such that the λ / 4 retardation layer of the laminate for transferring a circularly polarizing element, which is formed by laminating a polarizer and a λ / 4 retardation layer in this order on a release film, is disposed on the transparent substrate side; or (F) A step of laminating the laminate for transferring a circular polarization element, in which a λ / 4 retardation layer and a polarizer are laminated in this order on a release film, on a transparent substrate for a surface cover, so that the polarizer of the laminate for transferring a circular polarization element is disposed on the transparent substrate side. The transparent substrate is preferably a transparent substrate for use as a surface cover for an image display device.

[0111] (Image display device) As the image display device, any one having a function of preventing reflection by a circular polarizing element can be used without any particular limitation. The image display device preferably has a transparent conductive substrate having the above-mentioned circular polarizing element, a touch panel having a circular polarizing element, or a surface cover having a circular polarizing element. For example, the image display device preferably has a transparent conductive substrate, a circular polarizing element, and an image display cell in this order, a circular polarizing element, a transparent conductive substrate, and an image display cell in this order, a touch panel, a circular polarizing element, and an image display cell in this order, a circular polarizing element, a touch panel, and an image display cell in this order, or a surface cover, a circular polarizing element, and an image display cell in this order. In addition, as the image display device, for example, an organic EL display device, a micro LED display device, and the like are suitable examples. In addition, it can also be suitably used for a foldable type (foldable type) or a rollable type (rollable type) image display device. The image display device of the present invention can be made thin, and has good foldability and rollability.

[0112] In one embodiment, a method for producing an image display device having a circular polarizing element includes the steps of: (G) providing a touch panel having a circular polarization element on an image display device such that the touch panel is disposed on the viewing side (so that the circular polarization element is disposed on the image display cell side); (H) providing the touch panel having a circular polarization element on the image display device so that the circular polarization element of the touch panel is disposed on the viewing side (so that the touch panel is disposed on the image display cell side); or (I) A step of providing a transparent substrate for a surface cover having a circular polarizing element on an image display device so that the transparent substrate for a surface cover is disposed on the viewing side (so that the circular polarizing element is disposed on the image display cell side). It is preferred that the compound contains EXAMPLES

[0113] The present invention will be described in more detail below with reference to examples. The present invention is preferably a laminate for transferring a circularly polarizing element transferred to a transparent conductive substrate. The present invention is not limited to the following examples, and can be carried out by making appropriate modifications within the scope of the gist of the present invention. All of them are included in the technical scope of the present invention.

[0114] The retardation of the retardation layer in the laminate of the example was measured as follows.

[0115] (Retardation measurement of phase difference layer) An orientation control layer and a retardation layer were provided on the non-adhesive layer surface of a 50 μm thick polyester film (Cosmoshine (TM) A4100 manufactured by Toyobo Co., Ltd.) under the same conditions as in the examples described below, and this was transferred onto a glass plate (35 mm × 35 mm) to prepare a measurement sample. A UV-curable adhesive was used for the transfer. The retardation value (Re) of the sample was measured from the vertical direction using an automatic birefringence meter (KOBRA-WR, Oji Measurement Co., Ltd.) at a wavelength of 590 nm. Furthermore, the retardation value was similarly measured by tilting the film normal direction from 0 degrees to 50 degrees in 10 degree increments, with the slow axis in the film plane as the tilt axis (rotation axis). Rth was calculated from this value, the thickness, and the average refractive index. The thickness was determined by embedding the film in epoxy resin, cutting out a cross-sectional piece, and observing it under a polarizing microscope. The average refractive index was 1.60.

[0116] Each layer in the laminate of the examples is described below.

[0117] TIFF0007652069000001.tif110170

[0118] (Polarizer) (1) PVA polarizer transfer laminate As a thermoplastic resin substrate, polyethylene terephthalate with an intrinsic viscosity of 0.62 dl / d was melted and kneaded in an extruder, then extruded into a sheet on a cooling roll to produce an unstretched film with a thickness of 100 μm. An aqueous solution of polyvinyl alcohol with a degree of polymerization of 2400 and a degree of saponification of 99.9 mol% was applied to one side of this unstretched film and dried to form a PVA layer. The obtained laminate was stretched twice in the longitudinal direction between rolls with different peripheral speeds at 120° C. and taken up. Next, the obtained laminate was treated with a 4% boric acid aqueous solution for 30 seconds, and then immersed in a mixed aqueous solution of iodine (0.2%) and potassium iodide (1%) for 60 seconds to dye it, and subsequently treated with a mixed aqueous solution of potassium iodide (3%) and boric acid (3%) for 30 seconds. Furthermore, this laminate was uniaxially stretched in the longitudinal direction in a mixed aqueous solution of boric acid (4%) and potassium iodide (5%) at 72°C, subsequently washed with a 4% aqueous solution of potassium iodide, the aqueous solution was removed with an air knife, and then dried in an oven at 80°C. Both ends were slit and wound up to obtain a laminate for PVA polarizer transfer with a width of 50 cm and a length of 1000 m. The total stretching ratio was 6.5 times, and the thickness of the PVA polarizer was 5 μm. The thickness was measured by embedding the laminate for PVA polarizer transfer in epoxy resin, cutting out a slice, and observing it with an optical microscope. This PVA polarizer is labeled as PVA in Table 1.

[0119] (2) Liquid crystal polarizer The following compounds (d) and (e) were synthesized according to the description in paragraph

[0134] of JP-A 2007-510946 and Lub et al. Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996). [ka] [ka] The following dye (f) was synthesized according to Example 1 of JP-A-63-301850. [ka] The following dye (g) was synthesized according to Example 2 of JP-B-5-49710. [ka] The following dye (h) was synthesized according to the method for producing the compound of formula (1) described in JP-B-63-1357. [ka]

[0120] 75 parts by mass of (d), 25 parts by mass of (e), 2.5 parts by mass of (f), 2.5 parts by mass of (g), 2.5 parts by mass of (h), 6 parts by mass of IRGACURE (trademark) 369E (manufactured by BASF), and 250 parts by mass of ortho-xylene were mixed and dissolved to prepare a coating material for liquid crystal polarizers. The liquid crystal polarizer obtained by coating this coating material is indicated as liquid crystal coating in Table 1.

[0121] Example 1 (Preparation of Laminate 1 for Retardation Layer Transfer) A coating material for the orientation control layer was applied to the non-adhesive layer surface of a 50 cm wide polyester film (Cosmoshine (TM) A4100, manufactured by Toyobo Co., Ltd., thickness 50 μm) and dried at 100 ° C to form an orientation control layer with a thickness of 0.5 μm. The orientation control layer was then treated with a rubbing roll wrapped with a nylon napped cloth. The film was slanted on the rubbing roll, and the direction of the rubbing roll, the running speed of the film, and the number of revolutions of the rubbing roll were adjusted so that the rubbing direction was 45 degrees to the flow direction of the film. Subsequently, the coating material for the retardation layer was applied, and the film was heated at 110 ° C for 3 minutes to evaporate the solvent and align the rod-shaped liquid crystal compound. The film was then irradiated with ultraviolet light for 30 seconds in an environment of 110 ° C to obtain a retardation layer transfer laminate 1 with a length of 200 m. The retardation layer had a Re of 140 nm and a Rth of 70 nm.

[0122] The PVA polarizer transfer laminate and the retardation layer transfer laminate 1 were unwound, an ultraviolet-curing adhesive was applied to the polarizer surface (PVA surface) of the PVA polarizer transfer laminate, the adhesive surface was superposed on the retardation layer surface of the retardation layer transfer laminate 1, and then the laminate was irradiated with ultraviolet light from the retardation layer transfer laminate side to bond them together and taken up, to obtain a 200m long roll of the circular polarization element transfer laminate (CP1). Note that in CP1, the thermoplastic resin substrate of the PVA polarizer transfer laminate and the polyester film of the retardation layer transfer laminate 1 were peeled off immediately before being transferred to the target object (ITO layer).

[0123] Example 2 The coating material for the orientation control layer was applied to the polarizer surface of the PVA polarizer transfer laminate, and dried at 100°C to provide an orientation control layer with a thickness of 0.5 μm. The orientation control layer was then treated with a rubbing roll wrapped with a nylon napped cloth. The rubbing direction was 45 degrees to the flow direction of the film. Subsequently, the coating material for the retardation layer was applied, and the film was heated at 110°C for 3 minutes to evaporate the solvent and align the rod-shaped liquid crystal compound. Furthermore, the film was irradiated with ultraviolet light for 30 seconds in an environment of 110°C to obtain a laminate for transferring a circularly polarizing element (CP2). The Re of the retardation layer was 140 nm.

[0124] Example 3 A coating material for an orientation control layer was applied to the non-adhesive layer surface of a 50 cm wide polyester film (Cosmoshine (TM) A4100 manufactured by Toyobo Co., Ltd., thickness 50 μm), and dried at 100 ° C to provide an orientation control layer with a thickness of 0.5 μm. Furthermore, the orientation control layer was treated with a rubbing roll wrapped with a nylon raised cloth. The rubbing direction was performed so as to be the flow direction of the film. Thereafter, a coating material for a liquid crystal polarizer was applied to the rubbed surface, and dried at 110 ° C for 3 minutes to form a film with a thickness of 2 μm, and then irradiated with ultraviolet light to obtain a liquid crystal polarizer transfer laminate. Subsequently, an orientation control layer and a retardation layer were provided on the polarizer surface of this liquid crystal polarizer transfer laminate in the same manner as in Example 2, and a circularly polarized element transfer laminate (CP3) was wound into a roll with a length of 200 m.

[0125] Example 4 A hard coat layer coating material was applied to the non-adhesive layer surface of a 50 cm wide polyester film (Cosmoshine (TM) A4100 manufactured by Toyobo Co., Ltd., thickness 50 μm), dried in an oven at 90 ° C. to evaporate the solvent, and then irradiated with ultraviolet light to form a hard coat layer with a thickness of 3 μm. The hard coat layer was further treated with a rubbing roll wrapped with a nylon napped cloth. The rubbing direction was parallel to the flow direction of the film. Thereafter, in the same manner as in Example 3, a liquid crystal polarizer coating material was applied to the rubbed surface to obtain a liquid crystal polarizer transfer laminate. A retardation layer was provided on the polarizer surface of this liquid crystal polarizer transfer laminate in the same manner as in Example 2, and a circularly polarizing element transfer laminate (CP4) was wound into a roll with a length of 200 m.

[0126] The configurations of Examples 1 to 4 are shown in Table 1. [Table 1]

[0127] Example 5 A laminate for transferring a retardation layer was prepared by corona treatment of the non-adhesive layer surface of a polyester film, and a retardation layer was provided on this corona-treated surface (a laminate for transferring a retardation layer 2). Except for this, a roll of a laminate for transferring a circularly polarizing element (CP5) having a length of 200 m was obtained in the same manner as in Example 1. In addition, in CP5, the thermoplastic resin substrate of the laminate for transferring a PVA polarizer is peeled off immediately before transferring to an object (glass substrate).

[0128] Example 6 A coating material for an orientation control layer was applied to the retardation layer surface of the retardation layer transfer laminate 1, and dried at 100°C to provide an orientation control layer with a thickness of 0.5 μm. The orientation control layer was then treated with a rubbing roll wrapped with a nylon napped cloth. The rubbing direction was set to the flow direction of the film. Thereafter, a coating material for a liquid crystal polarizer was applied to the rubbed surface, and dried at 110°C for 3 minutes to form a film with a thickness of 2 μm. After that, ultraviolet rays were applied to obtain a laminate for transferring a circularly polarizing element (CP6), which was then wound into a roll with a length of 200 m.

[0129] Example 7 The liquid crystal polarizer transfer laminate of Example 3 and the retardation layer transfer laminate 2 of Example 5 were unwound, an ultraviolet-curing adhesive was applied to the polarizer surface of the liquid crystal polarizer transfer laminate, the adhesive surface was superposed on the retardation layer surface of the retardation layer transfer laminate 2, and then the laminate was irradiated with ultraviolet light from the retardation layer transfer laminate side to bond them together and taken up, thereby obtaining a roll of a circularly polarizing element transfer laminate (CP7) having a length of 200 m. Note that in CP7, the polyester film of the liquid crystal polarizer transfer laminate is peeled off immediately before it is transferred to the target object (glass substrate) before use.

[0130] The configurations of Examples 5 to 7 are shown in Table 2.

[0131] [Table 2]

[0132] Rating 1 The laminate for transferring a circularly polarizing element (CP1) was unwound and cut to the required size, and then the polyester film of the laminate for transferring a retardation layer 1 was peeled off. The ITO surface of a glass substrate on which ITO was laminated was attached to this peeling surface (orientation control layer surface) using an optical adhesive sheet, and the thermoplastic resin substrate (release film) of the laminate for transferring a PVA polarizer was peeled off from the obtained laminate. Subsequently, an optical adhesive sheet was attached to the peeling surface, and further, the ITO surface of a transparent conductive polyester film having an ITO layer on one surface and a hard coat layer on the other surface, which was separately prepared, was attached to produce a touch sensor model equipped with a circularly polarizing element. The obtained touch sensor model was placed on an organic EL display device with the glass surface facing down, and the anti-reflection effect was confirmed. It was found that the reflection of wiring and the like was reduced and that the touch sensor had a high anti-reflection effect.

[0133] Using the laminates CP2 and CP3 for transferring circular polarizers, touch sensor models equipped with circular polarizers were similarly prepared and evaluated, and it was found that they had a high anti-reflection effect. In CP2 and CP3, the ITO surface of the glass substrate was attached to the retardation layer surface using an optical adhesive sheet. In addition, in the case of CP3, when attaching to the ITO surface of the transparent conductive polyester film, the polyester film of the laminate for transferring liquid crystal polarizers was peeled off, instead of the thermoplastic resin substrate of the laminate for transferring PVA polarizers.

[0134] Rating 2 A touch sensor model was prepared by bonding the ITO surface of an ITO-laminated glass substrate and the ITO surface of an ITO-laminated TAC film together using an optical adhesive. The laminate for transferring a circularly polarizing element (CP4) was unwound and cut into a required size, and then the polyester film of the laminate for transferring a retardation layer 1 was peeled off. The CP4 retardation layer was attached to the TAC film surface of the touch sensor model using an optical adhesive, and then the polyester film of the liquid crystal polarizer transfer laminate was peeled off to produce a touch sensor model equipped with a circular polarizing element. The obtained touch sensor model was placed on top of an organic EL display with the glass side facing down to check the anti-reflection effect, and it was found that the reflection of the wiring, etc. was reduced, providing a high anti-reflection effect.

[0135] Rating 3 A touch sensor model was prepared by bonding the ITO surface of a glass substrate with ITO laminated thereon to the ITO surface of a transparent conductive polyester film with an ITO layer on one side and a hard coat layer on the other side using an optical adhesive. The laminate for transferring a circular polarizing element (CP5) was unwound and cut to a required size, and then the thermoplastic resin substrate of the laminate for transferring a PVA polarizer was peeled off. The CP5 polarizer surface (PVA surface) was attached to the glass surface of the touch sensor model using an optical adhesive, and then the polyester film of the retardation layer transfer laminate was peeled off to create a touch sensor model equipped with a circular polarizing element. The obtained touch sensor model was placed on top of an organic EL display device with the circular polarizing element side facing down to check the anti-reflection effect. It was found that the reflection of the wiring, etc. was reduced, providing a high anti-reflection effect.

[0136] Using the laminates for transferring circular polarizer CP6 and CP7, touch sensor models equipped with circular polarizers were similarly prepared and evaluated, and it was found that they had a high anti-reflection effect. For CP6, the liquid crystal polarizer surface was attached to the glass surface of the touch sensor model using an optical adhesive sheet. For CP7, when attaching to the glass surface of the touch sensor model, the polyester film of the laminate for transferring liquid crystal polarizer was peeled off, instead of the thermoplastic resin substrate of the laminate for transferring PVA polarizer.

[0137] In evaluations 1, 2, and 3, the circular polarization element function could be incorporated into the touch sensor without a significant increase in thickness.

[0138] Rating 4 The laminate for transferring a circularly polarizing element (CP5) was unwound and cut to the required size, and then the thermoplastic resin substrate of the laminate for transferring a PVA polarizer was peeled off. The polarizer surface was bonded to a polycarbonate sheet having a thickness of 1 mm using an optical pressure-sensitive adhesive sheet to obtain a polycarbonate sheet laminated with a circularly polarizing element. The polycarbonate sheet with the obtained circular polarizing element laminated thereon was placed on top of an organic EL display device with the circular polarizing element side facing down, and the anti-reflection effect was confirmed. It was found that reflections from wiring, etc. were reduced, providing a high anti-reflection effect. The resulting polycarbonate sheet laminated with the circular polarizing element can be used as a front cover sheet for an organic EL display device having an anti-reflection function without increasing the thickness substantially.

Claims

1. A method for manufacturing a laminate for transferring a circular polarization element, comprising a step of laminating a polarizer and a λ / 4 retardation layer in this order on a release film, or a step of laminating a λ / 4 retardation layer and a polarizer in this order on a release film, wherein the polarizer is uniaxially stretched polyvinyl alcohol (PVA) to which iodine or an organic dichroic dye has been adsorbed, and the method for manufacturing the laminate for transferring a circular polarization element does not use a self-supporting polarizer protective film.

2. A method for manufacturing a laminate for transferring a circular polarization element as described in claim 1, wherein the λ / 4 phase difference layer is provided by applying a paint for a λ / 4 phase difference layer directly to the polarizer, or by providing an orientation control layer directly on the polarizer and applying a paint for a λ / 4 phase difference layer on top of the orientation control layer, or by being attached to the polarizer using an adhesive or pressure-sensitive adhesive.

3. The method for producing a laminate for transferring a circular polarization element according to claim 1 or 2, wherein the polarizer is provided by any one of the following methods (a), (b1), and (b2). (a) A method in which a PVA polarizer alone is attached to the release surface of a release film or to the λ / 4 retardation layer on a release film using an adhesive or pressure sensitive adhesive. (b1) A method of transferring a PVA polarizer on a releasable substrate to a release surface of a release film or a λ / 4 retardation layer on a release film (b2) A method in which PVA is coated on a releasable substrate, and stretched together with the releasable substrate to allow iodine or an organic dichroic dye to be adsorbed into the PVA, and then the orientation is fixed with a boron compound to convert the releasable substrate into a releasable film.

4. A method for producing a transparent conductive substrate having a circular polarization element, comprising the steps of: (A) a step of laminating a laminate for transferring a circular polarization element produced by the production method according to any one of claims 1 to 3 on a transparent conductive substrate so that the laminate for transferring a circular polarization element is arranged in the order of a release film, a polarizer, a λ / 4 retardation layer, and a transparent conductive substrate; or (B) A step of laminating the laminate for transferring a circular polarization element produced by the production method according to any one of claims 1 to 3 on a transparent conductive substrate in the order of a release film, a λ / 4 retardation layer, a polarizer, and a transparent conductive substrate. A method comprising:

5. A method for manufacturing a touch panel having a circular polarization element, comprising the steps of: (C) A step of laminating the laminate for transferring a circular polarization element produced by the production method according to any one of claims 1 to 3 on a transparent conductive substrate of a touch panel so that the laminate for transferring a circular polarization element is arranged in the order of a release film, a polarizer, a λ / 4 retardation layer, and a transparent conductive substrate; or (D) A step of laminating the laminate for transferring a circular polarization element produced by the production method according to any one of claims 1 to 3 on a transparent conductive substrate of a touch panel in the order of a release film, a λ / 4 retardation layer, a polarizer, and a transparent conductive substrate. A method comprising:

6. A method for manufacturing an image display device having a circular polarization element, comprising the steps of: A method comprising a step of providing a touch panel having a circular polarization element manufactured by the manufacturing method according to claim 5 to an image display device such that the touch panel or the circular polarization element of the touch panel is arranged on a viewing side.

7. A method for producing a transparent substrate for a surface cover having a circular polarizing element, comprising the steps of: (E) A step of laminating the laminate for transferring a circularly polarizing element produced by the production method according to any one of claims 1 to 3 on a transparent substrate for a surface cover in the order of a release film, a polarizer, a λ / 4 retardation layer, and a transparent substrate for a surface cover; or (F) A step of laminating the laminate for transferring a circularly polarizing element produced by the production method according to any one of claims 1 to 3 on a transparent substrate for a surface cover in the order of a release film, a λ / 4 retardation layer, a polarizer, and a transparent substrate for a surface cover. A method comprising:

8. A method for manufacturing an image display device having a circular polarization element, comprising the steps of: A method comprising a step of providing an image display device with a transparent substrate for a surface cover having a circular polarizing element manufactured by the manufacturing method according to claim 7 so that the transparent substrate for a surface cover is positioned on the viewing side.

Citation Information

Patent Citations

  • Load module preparing system

    JP1989070829A

  • Polarizing film, optical film laminate including polarizing film, stretched laminate for use in manufacturing optical film laminate including polarizing film and method for manufacturing the same, and organic el display device having polarizing film

    JP2012134117A

  • Circularly polarizing plate and display device

    JP2014063143A

  • Sensor electrode substrate for touch panel integrated type organic electroluminescent display device, touch panel integrated type organic electroluminescent display device and manufacturing method of touch panel integrated type organic electroluminescent display device

    JP2017084153A

  • Decorative member, display device, and method for manufacturing organic electroluminescence display device

    JP2017128004A